Swing Boat: Inducing and Recording Locomotor Activity in a Drosophila melanogaster Model of Alzheimer’s Disease - Berlandi, Johannes; Lin, Fang-Ju; Ambrée, Oliver; Rieger, Dirk; Paulus, Werner; Jeibmann, Astrid (Frontiers in Behavioral Neuroscience, 2017)
Abstract Recent studies indicate that physical activity can slow down progression of neurodegeneration in humans. To date, automated ways to induce activity have been predominantly described in rodent models. To study the impact of activity on behavior and survival in adult Drosophila melanogaster we aimed to develop a rotating tube device “swing boat” which is capable of monitoring activity and sleep patterns as well as survival rates of flies. For the purpose of a first application we tested our device on a transgenic fly model of Alzheimer’s disease. Activity of flies was recorded in a climate chamber using the Drosophila Activity Monitoring System connected to data acquisition software. Locomotor activity was induced by a rotating tube device “swing boat” by repetitively tilting the tubes for 30 minutes per day. A non-exercising group of flies was used as control and activity and sleep patterns were obtained. The GAL4-/UAS system was used to drive pan-neuronal expression of human Aß42 in flies. Immunohistochemical stainings for Aß42 were performed on paraffin sections of adult fly brains. Daily rotation of the fly tubes evoked a pronounced peak of activity during the 30 minutes exercise period. Pan-neuronal expression of human Aß42 in flies caused abnormalities in locomotor activity, reduction of life span and elevated sleep fragmentation in comparison to wild type flies. Furthermore, the formation of amyloid accumulations was observed in the adult fly brain. Gently induced activity over 12 days did not evoke prominent effects in wild type flies but resulted in prolongation of median survival time by seven days (32.6%) in Aß42-expressing flies. Additionally, restoration of abnormally decreased night time sleep (10%) and reduced sleep fragmentation (28%) were observed compared to non-exercising Aß42-expressing flies. On a structural level no prominent effects regarding prevalence of amyloid aggregations and Aß42 RNA expression were detected following activity induction. The rotating tube device successfully induced activity in flies shown by quantitative activity analysis. Our setup enabled quantitative analysis of activity and sleep patterns as well as of survival rates. Induced activity in a Drosophila model of Alzheimer’s disease improved survival and ameliorated sleep phenotypes.